HUBUNGAN USIA KEHAMILAN DENGAN KEJADIAN STRETCH MARK PADA IBU HAMIL DI PUSKESMAS BERGAS - Febriyanti Dwi Prakasiwi; Eko Mardiyaningsih (Jurnal Ilmu Keperawatan Maternitas, 2023)
Background : Stretch marks appear during pregnancy because the skin is stretched. During pregnancy there are various kinds of signs that affect or are related to the shape of the skin of a woman who is pregnant, one of which is the appearance of stretch marks. The purpose of this study was to determine the relationship between gestational age and the incidence of stretch marks in pregnant women at the Bergas Health Center.Methods: This research design is correlative. The population in this study were all pregnant women who were examined at the Bergas Health Center, namely 111 people with a sample of 87 people who were taken using a purposive sampling technique. Measuring tool used in data collection is a questionnaire. Data were analyzed using the chi square statistical test using SPSS data processing software.Results: 30 out of 87 respondents (34.5%) gestational age of pregnant women at Bergas Health Center with 24-30 weeks of gestation and 57 of 87 respondents (65.5%) of 31-40 weeks of gestation, the severity of stretch marks for pregnant women at the Health Center There were 12 out of 87 respondents (13.8%) with mild gas category and 47 out of 87 respondents (49.3%) in the severe category. There is no significant relationship between gestational age and the incidence of stretch marks in pregnant women at the Bergas Health Center with a p value of 0.223 > α (0.05).